2020
DOI: 10.3389/fpsyg.2020.01683
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness, Compassion, and Self-Compassion Among Health Care Professionals: What's New? A Systematic Review

Abstract: Health care professionals (HCPs) are a population at risk for high levels of burnout and compassion fatigue. The aim of the present systematic review was to give an overview on recent literature about mindfulness and compassion characteristics of HCPs, while exploring the effectiveness of techniques, involving the two aspects, such as MBSR or mindfulness intervention and compassion fatigue-related programs. A search of databases, including PubMed and PsycINFO, was conducted following the Preferred Reporting It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
87
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(112 citation statements)
references
References 187 publications
(262 reference statements)
10
87
2
3
Order By: Relevance
“…Finally, the serial mediating roles of mindfulness and counselor’s self-efficacy were found in the present study, which could be supported by previous empirical findings ( Brown et al, 2017 ; Conversano et al, 2020 ). Previous studies found that mindfulness had a negative association with self-oriented empathy, and a moderate, negative association with CF ( Brown et al, 2017 ; Silver et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Finally, the serial mediating roles of mindfulness and counselor’s self-efficacy were found in the present study, which could be supported by previous empirical findings ( Brown et al, 2017 ; Conversano et al, 2020 ). Previous studies found that mindfulness had a negative association with self-oriented empathy, and a moderate, negative association with CF ( Brown et al, 2017 ; Silver et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies found that mindfulness had a negative association with self-oriented empathy, and a moderate, negative association with CF ( Brown et al, 2017 ; Silver et al, 2018 ). However, studies undertaken so far have provided inconsistent evidence regarding the effectiveness of mindfulness-based interventions on CF ( Duarte and Pinto-Gouveia, 2017a ; Steinberg et al, 2017 ; Wylde et al, 2017 ; Conversano et al, 2020 ). This inconsistency indicates that in addition to mindfulness training, other factors should be added in interventions in order to improve the intervention effectiveness on CF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, this mindfulness ability seems to be related to other psychological constructs such as emotional intelligence, vivid perception, receptive attention, personality traits, and defense mechanisms (Salovey et al, 1995;Costa and McCrae, 2008;Marazziti et al, 2015;Di Giuseppe et al, 2019a). Mindfulness has also been proven to represent a good predictor of depression, anxiety, stress, and well-being in association with self-compassion, selfefficacy, and gender (Soysa and Wilcomb, 2015;Conversano et al, 2020a). Dispositional mindfulness has the potential to be used as treatment for stress-related and other mental health disorders (Baer, 2003;Chang et al, 2004) and is effective in the enhancement of immune function (Davidson et al, 2003) and self-regulation, through the training of attention control, emotion regulation, and self-awareness (Tang et al, 2015;Geng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, several studies have shown that the maintenance of a healthy psychological state can be beneficial for reducing distress not only among subjects with psychopathological problems ( Marchetti et al, 2019 ; Rosa et al, 2019 ; Vicario et al, 2019 ) but also among patients with chronic medical conditions ( Di Giuseppe et al, 2018 , 2019 , 2020 ; Quattropani et al, 2018b ; Martino et al, 2020a ). Similarly, several studies have recently highlighted the importance of clinical psychological features in handling the consequences of age-related medical conditions for both patients ( Quattropani et al, 2018a ; Catalano et al, 2019 , 2020 ; Kelly et al, 2019 ; Marchi et al, 2019 ; Martino et al, 2020c ) and health professionals ( Quattropani et al, 2017 ; Conversano et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%